Achievement Of Online Piano Learning At University - Rachmajumadila Agustint; Rita Milyartini (Institut Seni Indonesia Surakarta, 2022)
Online piano learning occurs because of the development of increasingly advanced technology. Learning that was initially only carried out face to face directly had a time limit so that with the development of technology students could learn with various types of media used. Various kinds of media used by teachers improve student learning outcomes and motivate students to learn piano online. The purpose of writing this article is to see how the achievement of piano learning is carried out online through the use of various learning media. This article is based literature review on online piano learning published over the last ten years. Some data obtained a significant difference between the experimental class and the control class where student learning outcomes increased in the experiment class compared to the control class so that the use of online media in piano learning can improve student learning outcomes.KEYWORDS : Technology, Online piano learning, Variety of media, Achievement